Pesan Semiotis Kesalehan: Studi Analisis Ayat-ayat Filantropi Lembaga Amil Zakat Muhammadiyah dan Nahdlatul Ulama di Instagram - Irpan Sanusi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2022)
This article seeks to reveal the interpretation of piety from the Islamic philanthropic tradition (zakat, infaq, and alms) which has experienced both narrowing and development at the same time. In the realm of agency (perpetrators), muzakki are considered pious and generous people. Whereas zakat, essentially removes other people's property contained in our property. While in the social domain, there is a development of meaning if zakat is seen from a functional point of view. From a simple idea of giving transformed into a social movement for humanity. Through a semiological approach, it can reveal not only the linguistic meaning (denotational meaning) of the verses of the Qur'an related to Islamic philanthropy, but also continue to explore deeper such as symbolic meanings. The depth and specificity of the messages contained in the verses of the Qur'an are explored by continuing the process of subjective interpretation through the disclosure of further message connotations. This connotative meaning then becomes the basis for the formation of myths (philosophical meanings). This study finds the interpretation that piety according to Muhammadiyah is practicing al-Ma'un theology. A Muslim has not perfected his Islam if he has not practiced the essence of the values of Qs. Al-Ma'un. As for NU, it implies that piety has a practice based on the understanding of Ahl al-Sunnah wa al-Jama'ah. Although different in the basis of belief, both have similarities in philanthropic activities; strengthening of religious trends and religious symbols among urban communities and the middle class. In addition, between the two there is a tendency to collaborate rather than contest. Both of them confirmed as the guardian of wasatiyah Islam (guardian of wasatiyah Islam) in Indonesia.